Method of forecasting assessment of the maximum runoff characteristics of the Dnipro Basin's rivers in spring season - Zh. R. Shakirzanova; V. М. Boyko; M. V. Goptsiy; Е. І. Todorova; А. A. Dokus; Z. F. Serbova; N. N. Shvets (Український гідрометеорологічний журнал, 2018)
Introduction. In Ukraine, under the conditions of current climate variability, the water content of the rivers, including the period of spring flood, changes. Against the background of the general tendency of reduction of the runoff characteristics of the spring flood of the rivers in Ukraine, formation of catastrophic floods on rivers leading to flooding of territories and destruction of economic objects should not be ruled out. The research is aimed at solving an important scientific-applied and socio-economic problem of improving the water management in the basin of the country's large waterway, the Dnipro River, through probabilistic assessments of hydrological threats which include spring flood and its consequences – floods of various magnitudes. Therefore it is necessary to create a unified universal mathematical model for formation, calculation and long-term forecasting of water flood characteristics, and to implement it for the Dnipro Basin's rivers (including small ones which usually are not recorded in the data of runoff observations), taking into account the climate changes of the winter-spring period.